The Effect of Understanding Student Mental Health in Indonesia on Psychological First Aid - Rifa Madyana Putri (Universitas Pendidikan Indonesia (UPI), 2023)
The purpose of this study is to know the effect of mental health literacy among college students in Indonesia towards psychological first aid. The methods are literature review (library research) and questionnaires which are carried out through platforms in the Google Forms network to achieve broader quantitative data. Through descriptive analysis, which attempts to systematically describe the object of the study, then analyses the comparison of research discussions and distributing questionnaires to see their suitability with what is happening in the field. Data processing and analysis used are descriptive statistics. Results show that although mental health literacy is popular among college students, however, students do not know much about the impact of psychological first aid.